Rio Grande [videorecording (DVD)] - Ford, John, 1894-1973; Wayne, John, 1907-1979; O'Hara, Maureen, 1920-2015; Johnson, Ben, 1918-1996; Carey, Harry, Jr., 1921-2012; Bellah, James Warner, 1899-1976 (Republic Pictures Home Video ; Distributed by Artisan Home Entertainment, 2002)
A Cavalry unit on the Mexican border in the 1880s conducts a campaign against marauding Indians.